The Role of The Ministry of Law and Human Rights in Protecting Book Copyrights - Sabila, Shafiyyah Atina; Muh. Amiruddin; Jayadi, Ahkam; Natsif, Fadli Andi; Nurjannah, St. (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
This research explores the role of the Ministry of Law and Human Rights in protecting book copyrights and identifies the challenges it faces in this effort. Using a normative research approach, data was collected through literature studies and interviews with the Ministry's regional office in South Sulawesi. The findings reveal that the Ministry plays a key role in registering, monitoring, and educating the public about book copyrights. However, it faces challenges such as limited human resources and budget, the complexity of digital technology, low public awareness, and insufficient cross-sector cooperation, which hinder its efforts to protect book copyrights effectively.